PEMAHAMAN ISU GENDER MELALUI PEMBELAJARAN BERDIFERENSIASI BERBANTUAN LEARNER GENERATED DIGITAL MEDIA (LGDM ) - Gusti, Ririn; Putra, Ari (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2024)
This study aims to explore the use of Learner-Generated Digital Media (LGDM) in enhancing understanding of gender issues within the Gender in Education course. Using a qualitative approach, data were collected through in-depth interviews with learners, direct observations during learning sessions, and analysis of digital documents produced by learners. The findings reveal that LGDM encourages learners to participate more actively and engage deeply in the learning process. The use of digital media created by the learners themselves significantly enhances their understanding of gender issues. Moreover, LGDM supports learners in developing better critical and reflective skills through the production and analysis of digital media related to gender issues. This study highlights that the application of LGDM in learning can enrich the educational experience and deepen learners' comprehension of gender issues. It recommends integrating this method into broader gender education curriculam.